Feeling beyond rules: Politicising the sociology of emotion and anger in feminist politics - Holmes, Mary (European Journal of Social Theory, 2004)
The part anger plays in motivating political action is frequently noted, but less is said about ways in which anger continues to be a part of how people do politics. This article critically assesses approaches to emotions that emphasize managing anger in accordance with ‘feeling rules’. It reflects on the utility of Marxist notions of conflict as the engine of change for the understanding of how anger operates in political life. This involves understanding the ambivalence of anger and its operation within particular power relations. Shifting sets of conventions have had some continuity in discouraging women in Western nations (particularly white and middle-class women) from showing anger. But clearly, women do get angry and feminists have drawn on anger in acting politically. New Zealand feminist writings from the ‘second wave’ are taken as illustrative of the common difficulties Western feminists faced in dealing with anger. These difficulties were due to trying to juggle social conventions about femininity, the political ideal of sisterhood, and the realities of dealing with other women in often new and experimental political processes. Anger could be personalized and hurtful, but in certain cases its expression was constructive in producing more respectful relations. Exploring these cases makes it clear how anger produces, and is produced by, relations with others.
Keywords: 1900-1999; 1970-1979; 1980-1989; colère; discipline; débat; militance; mouvements féministes; nouvelle-zélande; océanie; périodes historiques; rapports de pouvoir; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions